2017
DOI: 10.7575/aiac.ijalel.v.6n.5p.83
|View full text |Cite
|
Sign up to set email alerts
|

Student Readiness in Learning Arabic Language based on Blended Learning

Abstract: Learning with technology or e-learning has been taking place in all areas of education including in learning and teaching of Arabic language. Despite the widespread use of e-learning for Arabic language, in line with the current technological advancements, the role of face-to-face classroom interactions must not be neglected. Face-to-face learning and e-learning have their own strengths.  Hence, a combination of both elements in teaching and learning as afforded by blended learning may be an excellent choice. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 4 publications
(4 reference statements)
1
17
0
Order By: Relevance
“…It could be assumed that the respondents might not feel comfortable and not be ready for a full online course in which they are required to perform learning process by themselves. This echoed by Osman and Hamzah (2017) who stated that the lowest mean score of the item on self-learning could reflect students' low readiness to learn on their own since they still relied on the teacher. On the other hand, the qualitative data analysis unveiled that online lessons were uninteresting for some students because the lessons were not engaging.…”
Section: Discussion and Recommendationsmentioning
confidence: 99%
See 3 more Smart Citations
“…It could be assumed that the respondents might not feel comfortable and not be ready for a full online course in which they are required to perform learning process by themselves. This echoed by Osman and Hamzah (2017) who stated that the lowest mean score of the item on self-learning could reflect students' low readiness to learn on their own since they still relied on the teacher. On the other hand, the qualitative data analysis unveiled that online lessons were uninteresting for some students because the lessons were not engaging.…”
Section: Discussion and Recommendationsmentioning
confidence: 99%
“…Nonetheless, using technology in learning was not barrier for students (Tang and Chaw, 2013). Furthermore, Osman and Hamzah (2017) found that the level of students' readiness was high for both face-to-face and online learning. On the other hand, the lowest mean score on the statement of self-learning indicated that the students might not be ready to learn on their own paces because they still relied on teachers' guidance.…”
Section: Literature Reviewmentioning
confidence: 90%
See 2 more Smart Citations
“…have their own laptops and students are internet-savvy. The study recommended the need for further studies to investigate the design and development of successful blended learning in teaching and learning Arabic language [20].…”
Section: Blended Learning In Afl and Aspmentioning
confidence: 99%